2012
DOI: 10.1371/journal.ppat.1002510
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Cellular miR-27 by a Novel, Highly Abundant Viral Transcript Is Important for Efficient Virus Replication In Vivo

Abstract: Cytomegaloviruses express large amounts of viral miRNAs during lytic infection, yet, they only modestly alter the cellular miRNA profile. The most prominent alteration upon lytic murine cytomegalovirus (MCMV) infection is the rapid degradation of the cellular miR-27a and miR-27b. Here, we report that this regulation is mediated by the ∼1.7 kb spliced and highly abundant MCMV m169 transcript. Specificity to miR-27a/b is mediated by a single, apparently optimized, miRNA binding site located in its 3′-UTR. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
195
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(208 citation statements)
references
References 46 publications
8
195
1
3
Order By: Relevance
“…Along these lines Marcinowski et al reported that during MCMV infection miR-27 had an increase in 3 0 end modifications as well as an increase in shorter (trimmed) sequences and that the tailed forms were more prevalent in total RNA compared to RNA isolated from Ago2 immuno-precipitation. 20 This model would be consistent with structural studies showing that pairing of a target to the 3 0 end of a DNA guide within bacterial Ago causes exposure of the guide strand 36 and pairing of a target at the 3 0 end of a miRNA increases its off rate from mammalian Ago2. 37 However Flores et al recently examined miRNA content inside and outside of RISC in mammalian cell lines and found that RISC-associated miRNAs were slightly more likely to have 3 0 end modifications.…”
Section: Destructive Regulators Of Mirnas: Recruiters Localizers or supporting
confidence: 80%
See 1 more Smart Citation
“…Along these lines Marcinowski et al reported that during MCMV infection miR-27 had an increase in 3 0 end modifications as well as an increase in shorter (trimmed) sequences and that the tailed forms were more prevalent in total RNA compared to RNA isolated from Ago2 immuno-precipitation. 20 This model would be consistent with structural studies showing that pairing of a target to the 3 0 end of a DNA guide within bacterial Ago causes exposure of the guide strand 36 and pairing of a target at the 3 0 end of a miRNA increases its off rate from mammalian Ago2. 37 However Flores et al recently examined miRNA content inside and outside of RISC in mammalian cell lines and found that RISC-associated miRNAs were slightly more likely to have 3 0 end modifications.…”
Section: Destructive Regulators Of Mirnas: Recruiters Localizers or supporting
confidence: 80%
“…We and others subsequently identified an MCMV transcript that directly associates with mature miR-27 and mediates its degradation. 19,20 The miR-27 binding site is within the 3 0 UTR of the m169 gene and mutation of this binding site results in virus attenuation following in vivo infection. 20 Also in 2010, a distantly related herpesvirus from squirrel monkeys, Herpesvirus saimiri (HVS), was shown to produce a small non-coding RNA, termed HSUR-1, which binds to the same cellular miRNA, and also mediates its degradation; 21 this is thought to be involved in activation and potentially transformation of T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas mature miRNAs generally are stable and tend to persist even if the processing enzymes are depleted by RNAi (46,47), examples are known in which specific miRNAs are degraded rapidly (48), and sequence-specific tailing and trimming was recently reported as a mechanism of miR-27a/b depletion in mouse (49). Our results show that 3′ adenylation of oncomiR miR-21 by the nucleotidyl transferase PAPD5 may similarly lead to its degradation by targeting it for 3′ end trimming by exoribonuclease PARN.…”
Section: Discussionmentioning
confidence: 99%
“…25 and 26), although a mechanism by which viral RNAs mediate the direct degradation of host miRNAs has been recently unveiled. [27][28][29] Several studies have explored the impact of apicomplexan parasites, many of which cause serious diseases in humans, on host microRNA expression during infection. Interestingly, modulation of host microRNA profiles was observed upon infection with several parasites, including Cryptosporidium parvum, 30,31 Plasmodium chabaudii, 32 Toxoplasma gondii 33 and Eimeria papillata.…”
Section: Microrna Responses To Pathogenic Bacteriamentioning
confidence: 99%